Factors Associated with Drain Output in Patients Undergoing to Parotidectomy - Iftikhar, Haissan; Dhanani, Rahim; Awan, Sohail; Zahid, Nida; Momin, Sehrish Nizar Ali (International Archives of Otorhinolaryngology, 2020)
Introduction Tumors of the parotid gland are heterogeneous. The purpose of the drain placement is to evacuate fluid that has a potential to accumulate in the dead space and cause infection after parotidectomy.Objectives To evaluate the factors associated with drain output among patients submitted to parotidectomy.Methods A retrospective cohort study was conducted in the Department of Otolaryngology/Head and Neck Surgery at the Aga Khan University Hospital, Karachi, from January 1994 to December 2014. Patients who underwent parotidectomy were included in the study. Linear regression analysis was used to determine the factors associated with drain output.Results A total of 193 patients were included in the study. The mean age of the patients was 46.3 years, and 57% of them were male. Length of surgery (β coefficient = 24.2; 95% confidence interval [95%CI]: 4.94–85.26), type of neck dissection (modified radical neck dissection: β = 93.9; 95% CI: 30.47–157.38; selective neck dissection: β = 79.9; 95%CI: 29.04–126.85), and type of parotidectomy (total β = 45.1; 95%CI: 4.94–85.26) were factors that significantly influenced drain output in patients submitted to parotidectomy with or without neck dissection.Conclusion Neck dissection, total parotidectomy and length of surgery were predictors of postoperative neck drainage in our cohort. These factors can help predict postoperative neck drain output and help in patient counselling.
Keywords: salivary glands; neoplasms; neck; infection; general surgery